Cost Management Capability and SME Profitability: An Integrative Approach to Cost Planning, Cost Management, and Cost of Goods Manufactured Accuracy - Andi Riska Andreani; Amiruddin Yunus; Rahmawati Rahmawati; Syafaruddin Syafaruddin (International Forum of Researchers and Lecturers, 2026)
Profitability is the primary indicator of SME business success; however, most Indonesian SME owners continue to face serious challenges in systematic cost planning, efficient cost management, and accurate cost of goods manufactured (CGM) calculation. This study analyzes the effects of cost planning (X₁), cost management (X₂), and CGM calculation accuracy (X₃) on SME profitability (Y), both partially and simultaneously, among production-sector SMEs in Makassar City. A quantitative approach with a cross-sectional explanatory survey design was employed. A purposive sample of 120 production-sector SME owners was selected. Data were collected using a structured Likert 1–5 questionnaire (23 items) and analyzed through descriptive statistics, validity and reliability tests (Cronbach's Alpha), classical assumption tests, multiple linear regression, F-test, t-test, and coefficient of determination using IBM SPSS Statistics 26. The F-test revealed that the three independent variables simultaneously exert a significant effect on SME profitability (F = 74.293; sig. = 0.000; R² = 0.659). Partially: cost planning (β = 0.391; t = 4.561; sig. = 0.000), cost management (β = 0.308; t = 3.382; sig. = 0.001), and CGM calculation accuracy (β = 0.251; t = 2.884; sig. = 0.005) each positively and significantly affect profitability. The three variables explain 65.9% of SME profitability variation. Cost planning is the strongest predictor of SME profitability, followed by cost management and CGM accuracy. Policy implications include the urgency of practice-based cost management training and CGM calculation mentoring for production-sector SME owners.